2016
DOI: 10.1038/srep30931
|View full text |Cite
|
Sign up to set email alerts
|

Non-monotonic temperature dependence of radiation defect dynamics in silicon carbide

Abstract: Understanding response of solids to particle irradiation remains a major materials physics challenge. This applies even to SiC, which is a prototypical nuclear ceramic and wide-band-gap semiconductor material. The lack of predictability is largely related to the complex, dynamic nature of radiation defect formation. Here, we use a novel pulsed-ion-beam method to study dynamic annealing in 4H-SiC ion-bombarded in the temperature range of 25–250 °C. We find that, while the defect recombination efficiency shows a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 36 publications
3
4
0
Order By: Relevance
“…Furthermore, in Ref. [19], a comprehensive analysis of RBS/Cderived depth profiles of disorder revealed anomalous features and pointed out to the crucial importance of radiation defect dynamics, as also confirmed in two other studies [20,21].…”
Section: Introductionsupporting
confidence: 71%
“…Furthermore, in Ref. [19], a comprehensive analysis of RBS/Cderived depth profiles of disorder revealed anomalous features and pointed out to the crucial importance of radiation defect dynamics, as also confirmed in two other studies [20,21].…”
Section: Introductionsupporting
confidence: 71%
“…It is seen that, for both Ne and Xe cases, n decreases with increasing t off , while the damage level at the sample surface remains unchanged, suggesting different dynamic mechanisms of bulk and surface disordering. This behavior is qualitatively similar to that previously reported in pulsed-beam studies of Si bombarded at room T with 500 keV Ne, Ar, Kr, or Xe ions, of 3 C -SiC irradiated at 100 °C with 500 keV Ar ions, and of 4 H -SiC bombarded with 500 keV Ar ions in the T range of 25–250 °C262728.…”
Section: Resultssupporting
confidence: 89%
“…Our recent work 24 25 26 27 28 29 has demonstrated that defect interaction dynamics can be accessed in experiments with pulsed ion beams when the Φ is delivered as a train of equal square pulses with a duration of t on and an instantaneous dose rate of F on , separated by a passive portion of the beam duty cycle of t off . Such pulsed beam experiments allow us to measure the characteristic DA time constant ( τ ) and the defect diffusion length ( L d ) by studying the dependence of stable lattice disorder on t off and t on , respectively 24 25 26 27 28 29 . We have recently measured a τ of ~3 ms and a L d of ~10 nm for 3 C -SiC bombarded at 100 °C with pulsed beams of 500 keV Ar ions 28 29 .…”
mentioning
confidence: 99%
“…Despite such similarity of the range of the τ values measured, the details of defect interaction dynamics are strongly material dependent. First, we note that these previous pulsed-beam studies of different materials 16 , 18 , 19 were performed at different T s. Only at 100 °C, do data sets for these four materials overlap, yielding τ 1 values of 8.9 ± 1.5, 0.98 ± 0.07, 4.6 ± 0.8, and 6.9 ± 1.2 ms for Ge, Si, 3 C -SiC, and 4 H -SiC, respectively, irradiated with 500 keV Ar ions 16 , 18 , 19 . Hence, among these four materials, Ge exhibits the slowest defect interaction dynamics at 100 °C (an order of magnitude slower than for Si).…”
Section: Resultsmentioning
confidence: 87%